IMPLEMENTASI PERATURAN ANGKUTAN UDARA KEBERANGKATAN DAN KEPULANGAN JAMAAH HAJI INDONESIA - Herawati Herawati (Institut Agama Islam Negeri Metro, 2022)
This study focuses on two issues, namely government policies regarding air travel for Indonesian pilgrims and the implementation of air travel services for pilgrims. Researchers used qualitative methods and descriptive analysis techniques in their research. The results of the study show that the government has implemented all regulations related to air transportation services for Indonesian pilgrims, both for departure and return services, although there are still some obstacles that are actually beyond the government's control. FDI Regulation No. 25 of 2015 also discusses the possibility of providing air transportation for pilgrims, including allowing airlines to take part in haj flight tenders with various administrative requirements to ensure that the aircraft is fit for haj pilgrimage flight operations from departure to return from Indonesia.